1981
DOI: 10.1042/bj1990383
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the fatty acid synthetase multienzyme complex from Euglena gracilis variety bacillaris

Abstract: A fatty acid synthetase multienzyme complex was purified from Euglena gracilis variety bacillaris. The fatty acid synthetase activity is specifically inhibited by antibodies against Escherichia coli acyl-carrier protein. The Euglena enzyme system requires both NADPH and NADH for maximal activity. An analysis was done of the steady-state kinetics of the reaction catalysed by the fatty acid synthetase multienzyme complex. Initial-velocity studies were done in which the concentrations of the following pairs of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…smegmatis [18, 291. It is also noted that the pyridine nucleotide requirement of the Euglenu mitochondrial system is different from those of the fatty-acid-synthetic systems in cytosol and chloroplasts of the same organism, which require NADPH for maximum activity [7,101. It has been demonstrated that E. gracilis cells gain ATP by the synthesis of wax esters from the reserve polysaccharide in anoxia, namely wax ester fermentation [I].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…smegmatis [18, 291. It is also noted that the pyridine nucleotide requirement of the Euglenu mitochondrial system is different from those of the fatty-acid-synthetic systems in cytosol and chloroplasts of the same organism, which require NADPH for maximum activity [7,101. It has been demonstrated that E. gracilis cells gain ATP by the synthesis of wax esters from the reserve polysaccharide in anoxia, namely wax ester fermentation [I].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction mixture contained in 0.3 ml, 0.5 mM [l-'4C]acetyl-CoA (0.05 pCi), 2mM NADH, 1 mM MgCI,, I00mM Hepes-KOH buffer, pH 7.0, and enzyme solution. When subcellular distribution of fatty acid synthesis from acetyl-CoA was determined NADPH was also added at 2 mM in the reaction mixture, since NADPH was reported to be required for maximum activity in cytosolic and microsomal fatty acid synthesis [7,111. The reaction was initiated by the addition of enzyme solution and conducted at 30 C for 1 h under aerobic or anaerobic conditions.…”
Section: Assay Of the Activity Of Fatty Acid Synthesis From Acetyl-coamentioning
confidence: 99%
“…The first two systems, localized in the chloroplasts, are acyl-carrier protein dependent systems (FAS II), which synthesize products with chain lengths of C16 and C18 that can be further elongated to C20-C24 (Ernst-Fonberg and Bloch 1971;Hendren and Bloch 1980). The third, a multifunctional fatty acid synthase (FAS I) located in the cytosol of Euglena, has as main products C16 fatty acids with C14 and as minor products C18 chain lengths (Goldberg and Bloch 1972;Walker et al 1981). The fourth is a microsomal fatty acid synthase activity (Khan and Kolattukudy 1973).…”
Section: Five Different Systems For Fatty Acid Synthesismentioning
confidence: 99%
“…The first two are acyl carrier proteindependent systems (FAS II) 1 localized in the chloroplasts and synthesize products with chain lengths of C16 and C18 that can be further elongated to C20 -C24 (10,11). The third, a multifunctional fatty acid synthase (FAS I) whose main products are C16 fatty acids with C14 and C18 chain lengths as minor products, is located in the cytosol of Euglena (12,13). The fourth is a microsomal fatty acid synthase activity (14).…”
mentioning
confidence: 99%